Cardiac Resynchronization Therapy Delivered Via a Multipolar Left Ventricular Lead is Associated with Reduced Mortality and Elimination of Phrenic Nerve Stimulation: Long‐Term Follow‐Up from a Multicenter Registry. (5th March 2015) - BEHAR, JONATHAN M.; BOSTOCK, JULIAN; ZHU LI, ADRIAN PO; CHIN, HUI MEN SELINA; JUBB, STEPHEN; LENT, EDWARD; GAMBLE, JAMES; FOLEY, PAUL W.X.; BETTS, TIM R.; RINALDI, CHRISTOPHER ALDO; HERRING, NEIL
Lower Mortality and Eliminated PNS Associated with Quadripolar Leads Introduction Cardiac resynchronization therapy (CRT) using quadripolar left ventricular (LV) leads provides more pacing vectors compared to bipolar leads. This may avoid phrenic nerve stimulation (PNS) and allow optimal lead placement to maximize biventricular pacing. However, a long‐term improvement in patient outcome has yet to be demonstrated. Methods A total of 721 consecutive patients with conventional CRTD criteria implanted with quadripolar (n = 357) or bipolar (n = 364) LV leads were enrolled into a registry at 3 UK centers. Lead performance and mortality was analyzed over a 5‐year period. Results Patients receiving a quadripolar lead were of similar age and sex to those receiving a bipolar lead, although a lower proportion had ischemic heart disease (62.6% vs. 54.1%, P = 0.02). Both groups had similar rates of procedural success, although lead threshold, impedance, and procedural radiation dose were significantly lower in those receiving a quadripolar lead. PNS was more common in those with quadripolar leads (16.0% vs. 11.6%, P = 0.08), but was eliminated by switching pacing vector in all cases compared with 60% in the bipolar group (P < 0.001). Furthermore, LV lead displacement (1.7% vs. 4.6%, P = 0.03) and repositioning (2.0% vs. 5.2%, P = 0.03) occurred significantly less often in those with a quadripolar lead. All‐cause mortality was also significantly lower in the quadripolar compared to bipolar lead group in univariate and multivariate analysis (13.2% vs. 22.5%, P < 0.001). Conclusions In a large, multicenter experience, the use of quadripolar LV leads for CRT was associated with elimination of PNS and lower overall mortality. This has important implications for LV pacing lead choice.